The role of androgens in women's health and wellbeing. (September 2021) - Bianchi, Vittorio E.; Bresciani, Elena; Meanti, Ramona; Rizzi, Laura; Omeljaniuk, Robert J.; Torsello, Antonio
Abstract: Androgens in women, as well as in men, are intrinsic to maintenance of (i) reproductive competency, (ii) cardiac health, (iii) appropriate bone remodeling and mass retention, (iii) muscle tone and mass, and (iv) brain function, in part, through their mitigation of neurodegenerative disease effects. In recognition of the pluripotency of endogenous androgens, exogenous androgens, and selected congeners, have been prescribed off-label for several decades to treat low libido and sexual dysfunction in menopausal women, as well as, to improve physical performance. However, long-term safety and efficacy of androgen administration has yet to be fully elucidated. Side effects often observed include (i) hirsutism, (ii) acne, (iii) deepening of the voice, and (iv) weight gain but are associated most frequently with supra-physiological doses. By contrast, short-term clinical trials suggest that the use of low-dose testosterone therapy in women appears to be effective, safe and economical. There are, however, few clinical studies, which have focused on effects of androgen therapy on pre- and post-menopausal women; moreover, androgen mechanisms of action have not yet been thoroughly explained in these subjects. This review considers clinical effects of androgens on women's health in order to prevent chronic diseases and reduce cancer risk in gynecological tissues. Graphical Abstract: ga1